“A Century of Orthodontic Progress” – Innovations in Orthodontics (Orthodontic Journal of Nepal, 2021)
Innovation is the roadmap towards improvement .Creation, implementation and execution of new ideas, methods and technology aiming at efficiency and improvement is known as innovation. Innovation is the roadmap towards improvement. The speciality of orthodontics has obtained new dimensions due to innovations such as holistic orthodontic approach, Laser assisted orthodontics, digitization in diagnosis and treatment planning, nanotechnology, genetically driven orthodontic treatment plans with gene therapy, interactive self ligating bracket and flash free adhesive coated appliance system, robotic wire bending, 3D bioprinted scaffolds to treat osseous defects of the craniofacial complex, forensic orthodontics, mobile apps in orthodontics and dentoalveolar distraction modalities. These innovations have lead to an accurate treatment with reduced clinician efforts, enhanced treatment precision and better patient compliance. The future of orthodontic speciality with these adjunts is bright and progressive. With reduced clinician’s efforts and improved patient’s compliance these advancement are certainly a boon to our orthodontic speciality